2015
DOI: 10.1016/j.precamres.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Crustal growth during island arc accretion and transcurrent deformation, Natal Metamorphic Province, South Africa: New isotopic constraints

Abstract: 15The Natal Metamorphic Province consists of, from north to south, the Tugela, Mzumbe, 16 and Margate terranes. These were accreted to the southeastern margin of the Kaapvaal 17Craton in the late Mesoproterozoic, and followed by intrusion of a large suite of A-type 18 granitoid bodies. New U-Pb data from zircon, titanite, and monazite further constrains the 19 temporal framework of these geological events. 20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Eglington et al 1989;Thomas & Eglington 1990). The superchondritic ε Hf -signatures of the granites reported in this study, also found in the data of Spencer et al (2015), add supporting evidence to the juvenile nature of the Natal Sector. The Namaqua Sector is therefore an unlikely source area for the generally juvenile, late Mesoproterozoic to earliest Neoproterozoic zircons found in the Natal Group (Fig.…”
Section: Potential Source Areassupporting
confidence: 87%
See 3 more Smart Citations
“…Eglington et al 1989;Thomas & Eglington 1990). The superchondritic ε Hf -signatures of the granites reported in this study, also found in the data of Spencer et al (2015), add supporting evidence to the juvenile nature of the Natal Sector. The Namaqua Sector is therefore an unlikely source area for the generally juvenile, late Mesoproterozoic to earliest Neoproterozoic zircons found in the Natal Group (Fig.…”
Section: Potential Source Areassupporting
confidence: 87%
“…Sm-Nd work has shown that, while the Natal Sector has a juvenile nature (Eglington et al 1989;Thomas & Eglington 1990), the Namaqua Sector has a more prolonged crustal history (Yuhara et al 2001;Pettersson et al 2009). The juvenile nature of the Natal sector is also supported by Hf data (Spencer et al 2015). The southern two-thirds of the Natal Sector are dominated by granitoid rocks which make up >80% of the exposed area (Eglington et al 2003).…”
Section: Geological Settingmentioning
confidence: 92%
See 2 more Smart Citations
“…Further north‐east, the basement is formed by 3.1 Ga granitoids of the Mpuluzi suite (Kröner et al , ). In the southern part of the study area, the Natal Suture Zone (Figure B) dated to 1.20–1.08 Ga is characterized by an array of major east‐west striking thrust faults that formed during the accretion of terranes to the Kaapvaal Craton (Spencer et al , ). Mainly south and east of the Natal Suture Zone, Siluro‐Ordovician clastic sedimentary rocks of the Natal Group cover the older basement and underlie the Dwyka Group (Marshall, ).…”
Section: Geological Settingmentioning
confidence: 99%